Análise da cinética do VO2 no domínio severo do crawl em condição atada de nado - Siqueira, Leandro Oliveira da Cruz [UNESP] (2015)
Major concernments about the available data on swimmer's aerobic capacity assessed during tethered-swimming are (1) devise technology to sample oxygen uptake (VO2), (2) temporal mismatching of gas exchange response to underlying physiological process, and (3) undiscernible markers for threshold discrimination from ventilatory parameters. Therefore, the aimed was designs an incremental tether-test (ITT) with step workload (WL) based on individual rates of maximal tether-force (Fmax) in crawl stroke, and thus identifies the lactate threshold (LT), by means of gas exchange response (GET), and respiratory compensation point (RCP). Eleven males (18.0 ± 4.0 years old, 180.2 ± 6.8 cm height, and 71.8 ± 9.5 kg body weight) and five females (16.8 ± 3.6 years old, 166.2 ± 5.5 cm height, and 61.1 ± 9.8 kg body weight) swimmers performed an ITT until volitional exhaustion attached to a weight-baring pulley-rope system to the assessment of GET, RCP and maximal aerobic power (VO2max). WL was incremented from 30 to 70% of Fmax, with step rate of 5% every minute. Fmax was measured with a 500kgf load cell attached to the swimmers by an inelastic rope, during full-crawl all-out bout lasting 30-s. Pulmonary gas exchange was sampled breath-by-breath (CPET K4b2) connected to a specific snorkel (new AquaTrainer). GET criteria were: rising in VE/VO2 with no concomitantly changes on VE/VCO2; and PCR criteria were: sustained increasing in both VE/VO2 and VE/VCO2. Mean VO2max approached 52.4 ± 4.9 mlO2×kg-1×min-1 and 45.4 ± 6.0 mlO2×kg-1×min-1 ...